The potential for mycobiont sharing between shrubs and seedlings to facilitate tree establishment after wildfire at Alaska arctic treeline. Issue 14 (18th May 2017) - Hewitt, Rebecca E.; Chapin, F. Stuart; Hollingsworth, Teresa N.; Taylor, D. Lee
Abstract: Root‐associated fungi, particularly ectomycorrhizal fungi (EMF), are critical symbionts of all boreal tree species. Although climatically driven increases in wildfire frequency and extent have been hypothesized to increase vegetation transitions from tundra to boreal forest, fire reduces mycorrhizal inoculum. Therefore, changes in mycobiont inoculum may potentially limit tree‐seedling establishment beyond current treeline. We investigated whether ectomycorrhizal shrubs that resprout after fire support similar fungal taxa to those that associate with tree seedlings that establish naturally after fire. We then assessed whether mycobiont identity correlates with the biomass or nutrient status of these tree seedlings. The majority of fungal taxa observed on shrub and seedling root systems were EMF, with some dark septate endophytes and ericoid mycorrhizal taxa. Seedlings and adjacent shrubs associated with similar arrays of fungal taxa, and there were strong correlations between the structure of seedling and shrub fungal communities. These results show that resprouting postfire shrubs support fungal taxa compatible with tree seedlings that establish after wildfire. Shrub taxon, distance to the nearest shrub and fire severity influenced the similarity between seedling and shrub fungal communities. Fungal composition was correlated with both foliar C:N ratio and seedling biomass and was one of the strongest explanatory variables predicting seedling biomass. While correlative, these results suggest that mycobionts are important to nutrient acquisition and biomass accrual of naturally establishing tree seedlings at treeline and that mycobiont taxa shared by resprouting postfire vegetation may be a significant source of inoculum for tree‐seedling establishment beyond current treeline.